COMPARATIVE OF REAL COST AGAINST THE PRICE OF INA-CBG’S BREAST CANCER AND ITS AFFECTING FACTORS IN JKN PROGRAM ERA - Arifin Santoso; Indriyati Hadi Sulistyaningrum; Abdur Rosyid; Erwin Budi Cahyono; Ken Wirastuti; Bagus Riyanto (Universitas Muhammadiyah Magelang, 2020)
This study aims to determine differences in real cost and INA CBG's rate and to find out the factors that influence the difference between the real cost and INA CBG's rate in patient with breast cancer in JKN Era at Sultan Agung Islamic Hospital between January 2017 and October 2017. This type of research is a non-experimental (observational) study, data taken retrospectively from hospital financial data and medical records of patients. Data analysis using Mann-Whitney is used to determine the suitability of real costs with INA CBG rates. and the Kruskal-Wallis test is used to find out what factors affect real costs. There was difference between the real cost and the INA CBG's rate for class 1 of Rp (-9,861,600), class 2 of Rp (30,643,000), and class 3 of Rp (146,724,100). The factors that influence the real costs were nursing class (p = 0.014) and Length of stay (p = 0.000). The conclusion of this study is that there is a difference between the real cost in patient with breast cancer in JKN Era at Sultan Agung Islamic Hospital between January 2017 and October 2017.